Khondakāra Bajalu Śāhera jībana o gāna - Śāha, Khondakāra Bajalu, 1914-2017; Sikadāra, Sumana, 1981- (Jhināidaha : Begabatī Prakāśanī, 2022)
Compilation of texts of Bengali folk songs by Khondakar Bajalu Shah, 1914-2017, Bengali mystic poet from Bangladesh.
Songs.
In Bengali.
Keywords: Songs, Bengali -- Bangladesh -- Texts; Folk songs, Bengali -- Bangladesh -- Texts; Chansons folkloriques bengali -- Bangladesh -- Textes; Folk songs, Bengali; Bangladesh; Texts